THE EFFECT OF INCENTIVES AND INFRASTRUCTURE GIVING ON EMPLOYEE JOB SATISFACTION AT PT. PERMODALAN NASIONAL MADANI MEKAAR JAMBI BRANCH - Fathir, Iqbal; Pratikno, Yuni; Ratnawita, Ratnawita (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
Using the simple random sampling technique, a sample of 43 employees was taken at PT. Permodalan Nasional Madani Mekaar Jambi Branch as respondents in this study. There is an influence of incentives on employee job satisfaction, as evidenced by the t-value for the Incentive variable (X1) of 7.504, while the t-table value for N = 43 is 2.016. So 7.504> 2.016, then H0 is rejected and Ha is accepted, it can be stated that Incentives (X1) have a significant effect on Employee Job Satisfaction (Y). There is an influence of Facilities and Infrastructure on employee job satisfaction, as evidenced by the t-value for the Facilities and Infrastructure variable (X2) of 6.184, while the t-table value for N = 43 is 2.016. So 6.184> 2.016, then H0 is rejected and Ha is accepted, it can be concluded that partially the Facilities and Infrastructure variable (X2) has an effect on Employee Job Satisfaction (Y). There is an influence of incentives and Facilities and Infrastructure together on employee job satisfaction. proven from the ANOVA test obtained the Fcount value of 237.192, while Ftable ( 0.05) for n = 43 is 2.82. So Fcount> from Ftable ( 0.05) or 237.192> 2.82 with a significant level of 0.000 because 0.000 <0.05, then it can be said that the Provision of Incentives (X1) and Facilities and Infrastructure (X2) together or simultaneously have a positive effect on Employee Job Satisfaction (Y). While the Adjusted R Square (R2) value is 0.918. This shows that 91.8% of Incentives (X1) and Facilities and Infrastructure (X2) together have an effect on Employee Job Satisfaction (Y), while the remaining 8.2% is influenced by other factors not examined in this study.